Competencias para la ciudadanía : reflexión, decisión, acción - Morillas Gómez, María Dolores (Colección Materiales 12/16 para Educación Secundaria ; Temas transversales., 2012)
An organized summary of the experience from the project Educación para la Ciudadanía that took place at the Instituto Veritas in Madrid, Spain. Divided in two parts: theory and introduction to the subject and educational applications.